Content Analysis of the Chernobyl Accident’s Impact on Value Sphere and Lifestyle Accident Liquidators - Golubenko, Olga (Psychological Prospects Journal, 2015)
This article contains a content analysis  of  the semantic   space   of  answers  of   Chernobyl  accident liquidators to questions of the author’s questionnaire. Questionnaire was developed to identify subjective assessment of transformation processes in the value sphere and the lifestyle of respondents. Structural components of the proposed questionnaire were subjective assessments of psychological consequences of participation in the mitigation work, changes in lifestyle over the last 28 years, radiation safety to the date, state and  society attitudes towards liquidators. Each of these components corresponds to a separate block of questions. An analysis of semantic groups allowed us to determine the percentage of people who felt emotional discomfort since the first days and proportion of those who almost did not feel negative consequences of traumatic situation for the psychological sphere and to track dynamic changes in psychological state, to get a conception regarding structural and destructive mechanisms to overcome  the negative effects of traumatic situations, qualitative data on changes in the value orientations. Also this article explores the features of transformation in the content and lifestyle of liquidators for the main areas, namely in the field of health, professional life, personal life, in the social sphere. As a result of the content analysis of questionnaire materials, changes in the value sphere and in the lifestyle sphere of Chernobyl accident liquidators were confirmed.